Leveraging learning analytics to support teachers’ professional development: insights from a digital application - Leibur, Tiiu; Saks, Katrin (Frontiers in Education, 2025)
This study investigates the effectiveness of a digital application with a Learning Analytics module in supporting teachers’ professional development. The user experience of unqualified teachers, qualified teachers and professional assessors is assessed to determine how the digital application contributes to understanding and progression towards higher levels of qualification. Learning Analytics is presented as a mechanism for identifying developmental needs, improving performance and fostering professional growth. The digital application allows for ongoing monitoring of teaching competences, self-assessment and feedback. The results show that the digital application effectively promotes self-development and improves pedagogical skills by enabling teachers to monitor their professional development progress and teaching practices. As a result, users report increased confidence and self-esteem, which highlights the role of the application in supporting continuous professional growth.